Life cycle assessment of a wiring harness - Martins, Patricia Sofia Pereira Soares (2023)
Growing concerns over energy and environmental sustainability have increased worldwide interest in more efficient and cleaner transportation systems and industrial activities. Today’s automotive wiring harness manufacturing process faces challenges concerning environmental issues and how manufacturers can produce a sustainable industry. This work was conducted to meet the interest of Yazaki Saltano in evaluating the environmental performance of wiring harnesses. The life cycle assessment (LCA) of a wiring harness was conducted, following a cradle-to-gate approach. The wiring harness is an assembly of wires and connections that runs through the vehicle, transferring signals and electrical power to electronic and electrical devices to guarantee the vehicle’s fundamental operations and safety. The environmental impact assessment method used was the ReCiPe midpoint 2016, encompassing the following environmental impact categories: global warming (GW), ozone formation, terrestrial ecosystem (OF,TE), terrestrial acidification (TA), freshwater eutrophication (FE), marine eutrophication (ME), mineral resource scarcity (MRS) and fossil resource scarcity (FRS). The impact results of the wiring harness LCA show that raw material production is the highest contributor (>87%) to the environmental impacts for all impact categories under study. Wires represented a higher environmental impact (>40%) face to the other wiring harness components (such as connectors, clips, terminals, etc.), mainly due to the utilization of conductive copper material. The wires evaluation revealed that wire 13 is a hotspot, representing (11% (OF,TE), and 12% (TA, FE, MRS)). Assy cables (assy cables A and B) were also identified as hotspots. The Assy cable B impact contribution ranges from 10% (GW and FRS) to 16% (MRS) and assy cable A from 9% (FE, (OF,TE)) to 11% (MRS). Clips and connector components revealed a significant contribution to the total environmental impacts, due to the plastic composition, accounting for the highest value of 21% (ME) and 12% (FRS), respectively. The reduction of the quantity of used raw materials, namely copper and plastics, and/or material substitution (e.g., aluminium, recycled copper instead of copper) can be a future strategy to be studied to make the wiring harness considerably more sustainable from an environmental point of view.